2016
DOI: 10.1088/0963-0252/25/1/015020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulse polarity on the temporal and spatial emission of an atmospheric pressure helium plasma jet

Abstract: A single needle-electrode plasma jet driven by a home-made microsecond pulse power supply is studied. The electrical characteristics and optical emissions of the plasma jets driven by positive-and negative-polarity pulses are compared. With the same magnitude of applied voltage, the plasma jet driven by positive pulses shows a higher discharge current, a higher optical emission intensity and travels to a longer distance. The temporal-spatially resolved He (706.5 nm), N 2 (337.1 nm) and + N 2 (391.4 nm) emissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…Notably, particularly the band of OH (A) is also expressed as the second diffraction band around 618 nm. These radical species are mainly generated by high‐energy electron excitation and the penning ionization process . The distinct structures of the spectra of He(2 1 P–4 1 F) and He (2 1 P–4 1 D) are shown in Figure b, which would be of use to analyze the electric field distribution from tube end to ITO surface for the two types of mode patterns in the study below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, particularly the band of OH (A) is also expressed as the second diffraction band around 618 nm. These radical species are mainly generated by high‐energy electron excitation and the penning ionization process . The distinct structures of the spectra of He(2 1 P–4 1 F) and He (2 1 P–4 1 D) are shown in Figure b, which would be of use to analyze the electric field distribution from tube end to ITO surface for the two types of mode patterns in the study below.…”
Section: Resultsmentioning
confidence: 99%
“…For He APPJ admixed with N 2 , more N 2 + (B) is generated through N 2 ‐electron reactions and the penning ionization reaction between metastable He(2s 1 S 0 ) (energy levels of 20.62 eV) and He(2s 3 S 1 ) (energy levels of 19.82 eV) . A small addition of N 2 can promote penning ionization, which reduces the initial discharge voltage, while a large number of N 2 molecules as the doping ratio increases can weaken penning ionization and enhance the breakdown voltage due to the high‐vibration dynamic diatomic structure of the N 2 molecule . However, superfluous N 2 also depletes the N 2 + (B) quantity that causes less N 2 + (B) formation.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental research showed that the APPJs are typically composed of discrete plasma bullets, which propagates with velocities on the order of 10 4 –10 6 m/s [52, 53]. Wang et al [54] investigated the spatial and temporal distribution of N 2 , N 2 + , O and He emission in a pulse‐driven helium plasma jet. The N 2 and N 2 + emission plume travelled at a faster speed and located in the plume front while He and O emission travelled at a slower speed and only located in the nozzle exit.…”
Section: Pulsed Discharge Plasma Characterisationmentioning
confidence: 99%
“…A plasma jet, generated in open air rather than in confined chambers, can be used for direct treatment without the limitation of the object’s size [19]. However, the treatment area of single plasma is small (less than 1 cm 2 ) due to its inherent structure [20]. One convenient method is to form a jet array by grouping a number of individual plasma jets units together.…”
Section: Introductionmentioning
confidence: 99%